Analisis Risiko Persediaan terhadap Kelancaran Produksi Studi Kasus PDAM Tirta Kahuripan Kabupaten Bogor - Achmad, Noor; Ningsih, Yuniarthi (Sekolah Tinggi Ilmu Ekonomi Kesatuan, 2006)
Inventory signifies much to manufacture company because it functions to relate between sequential operation in producing process of goods and its delivery to consumers, so that the availability of inventory enables production operation can be carried out because time factor among operation is able to be minimized. Basically inventory makes the process of production becomes easier that must be conducted sequentially to produce goods and deliver to consumers. Keywords: Inventory Risk, Production Process